First data on vocalization in Leiosaurus catamarcensis (Koslowsky, 1898) and Pristidactylus scapulatus Burmeister, 1861, (Iguania, Leiosauridae) from San Juan, Argentina - Laspiur, Alejandro (2007)
In Argentina not antecedents regarding to lizards vocalization studies exist. This work to seeks to highlight in two leiosaurid species (Leiosaurus catamarcensis and Pristidactylus scapulatus) the vocalization characteristics in order to evaluate potentially valid differences for systematic use. The vocalizations were registered in temperature controlled conditions and simulating aggressive encounters. The observed repertoire consists in two, warning (ADV) and attack (AT) vocalization components, different among themselves due to vocalization temporary length. L. catamarcensis and P. scapulatus vocalize in a same frequency rank, regardless to the vocalization type. Besides we find that the L. catamarcensis vocalizations were more prolongest than P. scapulatus.